Spider Web Graphic Organizer on Canva to increase students’ writing skills in caption text in the XII MIPA 4 SMAN 10 Semarang - Kurniawan, Muhamad Fajar (Prosiding Seminar Nasional Pendidikan Profesi Guru, 2023)
This research aims to see the impact of the Spider Web Graphic Organizer on Canva in improving students’ writing skills in the caption text in class XII MIPA 4 students at SMAN 10 Semarang. The research method used is Collaborative Classroom Action Research (PTK). The research subjects were students of class XII MIPA 4 SMA N 10 Semarang, with a total of 35 students. Data is collected through tests, observations, and documentation. The research results showed that there was an increase in skills in writing caption text. The average student scores obtained in the pre-cycle, cycle I, and cycle 2 were 69.31, 73.85, and 81.34 respectively. From the average obtained, it can be seen that there is a significant increase in the average score of students between pre-cycle and cycle 2 in the students’ skill of writing caption text.